2019
DOI: 10.1016/j.msard.2019.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Higher satisfaction and adherence with glatiramer acetate 40 mg/mL TIW vs 20 mg/mL QD in RRMS

Abstract: Background: Patients who perceive their medication to be ineffective or inconvenient are less likely to be adherent to treatment, with potentially significant consequences on long-term clinical outcomes. Many patients with multiple sclerosis (MS) are nonadherent to treatment despite demonstrated efficacy of disease-modifying therapies (DMTs). While glatiramer acetate (GA; Copaxone ® , Teva Pharmaceuticals) both 20 mg/mL once daily (GA20) and 40 mg/mL three times weekly (GA40) have demonstrated efficacy in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Our search retrieved 420 records with 53 eligible publications reporting on 48 trials 2269 (Appendices 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our search retrieved 420 records with 53 eligible publications reporting on 48 trials 2269 (Appendices 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Most trials assessed non-pharmacological interventions ( n = 41; 85%) with primarily lifestyle ( n = 18; 38%) and/or behavioral ( n = 13; 27%) components (Figure 1 and Table 3). Only seven trials assessed drugs (15%; alemtuzumab, 34 corticotrophin, 65,69 glatiramer acetate, 28 natalizumab, 60 interferon beta-1a, 67 and fingolimod); 64 these were published between 1967 and 2019 (median 2014) and had a median of 350 participants (IQR = 70–745; overall 3601). The most frequent comparator was usual care ( n = 25; 52%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall retention rate (60%) is supported by recent research demonstrating high patient satisfaction and adherence with GA40. 6,7 Another limitation is the lack of MRI data from three to seven years. The three-year results showed that ES and DS patients exhibited similar numbers of GdE T1 and new or enlarging T2 lesions 4 ; however, ES patients exhibited significantly smaller changes in gray matter volume than DS patients from Year 1 to Year 3 (mean difference, 0.371%; p = 0.02), with a similar trend in whole-brain volume ( p = 0.08).…”
Section: Discussionmentioning
confidence: 99%
“…5 A recent open-label study demonstrated significantly greater patient satisfaction, better treatment adherence, reduced impact of fatigue on patient activities, and improved patient-reported mental health for patients treated with GA40 versus GA20. 6 These significant differences were maintained over a 12-month period. 7 However, long-term data on the efficacy and safety of GA40 are lacking.…”
Section: Introductionmentioning
confidence: 85%